Formulasi dan Evaluasi Sunscreen Spray Gel Ekstrak Buah Kiwi (Actinidia deliciosa) sebagai Sun Protection - Sara Ayu Wulandari; Monica Anggraini; Mutiara Nabila; Muhamad Taswin; Ratnaningsih Dewi Astuti (Poltekkes Kemenkes Palembang, 2025)
Background: As a tropical country, Indonesia experiences high levels of sunlight year-round, increasing the risk of ultraviolet (UV) radiation exposure. Excessive UV exposure can cause various skin problems such as premature aging (photoaging), sunburn, hyperpigmentation, and even increased risk of skin cancer with long-term exposure. This underscores the importance of protecting the skin from the harmful effects of UV rays. Sunscreen is an effective form of protection against skin damage caused by UV radiation. However, most sunscreens on the market still use synthetic chemicals as UV filters. Several studies have reported that excessive use of chemical-based sunscreens can cause skin irritation, allergic reactions, and even impact the aquatic environment. This highlights the need for alternative natural sunscreens that are safer, more environmentally friendly, and still effective in protecting the skin. Kiwifruit (Actinidia deliciosa) is one natural ingredient with potential for development as a sunscreen. Kiwifruit is known to contain vitamin C, vitamin E, flavonoids, and polyphenol compounds with antioxidant properties. These compounds can help ward off free radicals, protect skin tissue from UV radiation damage, and maintain skin health. Several studies have also shown that antioxidant-rich fruit extracts can enhance the activity of natural sunscreens. Methods: This study was an experimental study, formulating a sunscreen spray gel from kiwifruit extract with varying extract concentrations in formula I (10%), formula II (15%), and formula III (20%). This experimental study aimed to develop a sunscreen spray gel containing kiwifruit extract as a natural sunscreen product that has the potential to protect the skin from ultraviolet radiation exposure. This research did not involve direct human testing, but instead focused on the extraction process, formulation, and physical evaluation of the preparation to assess the stability and quality characteristics of the developed product. Results: Kiwifruit (Actinidia deliciosa) extract could be formulated into a stable sunscreen spray gel preparation that met the requirements, with the most optimal extract concentration variation in formula II at 15%. The kiwifruit extract sunscreen spray gel met the stability requirements of physical tests, including homogeneity, pH, spreadability, viscosity, organoleptic (color, odor, clarity), and skin irritation tests during 28 days of storage at room temperature and after a cycling test. Conclusion: The kiwifruit extract was obtained through a maceration method using 70% ethanol as a solvent, chosen because it can extract both heat-stable and heat-stable active compounds. The sunscreen spray gel formula was created by varying the concentration of kiwifruit extract as the active ingredient in natural sunscreen. Product evaluation included various physical tests to ensure product stability, including homogeneity, pH, spreadability, viscosity, organoleptic, and skin irritation tests.